Inhibitory effect of carbon nanotubes with metabolites of Bacillus amyloliquefaciens on pathogenic fungi - Orozco-Plancarte, Antonio; Cerna-Chávez, Ernesto; Ochoa-Fuentes, Yisa María; Landeros-Flores, Jeronimo; Jasso-de Rodríguez, Diana; Medina-Ramírez, Iliana Ernestina; Olalde-Portugal, Víctor (Ecosistemas y Recursos Agropecuarios, 2022)
Diseases induced by phytopathogenic fungi generate considerable economic losses and severe damage to agricultural crops. The objective of this research was to evaluate the inhibitory effect in vitro of carbon nanotubes with extracts of Bacillus amyloliquefaciens on the mycelial development of Rhizoctonia solani (Rs), Fusarium solani (Fs), Colletotrichum acutatum (Ca) and Alternaria alternata (Aa). Data were analyzed using Probit, ANOVA analysis in a completely randomized design of five treatments with 20 repetitions and Tukey test (p 0.05). B. amyloliquefaciens extracts at high doses, inhibited 100% of mycelial growth but by using carbon nanotubes with extracts at low doses, a similar inhibitory effect of Rs, Fs, Ca and Aa (100, 90, 90 and 60%) respectively. The use of carbon nanotubes with extracts of B. amyloliquefaciens are an efficient alternative in the in vitro control of phytopathogenic fungi.